Adductor canal block (ACB) plus infiltration of the posterior capsule of the knee (iPACK) block versus 4-in-1 block in an arthroscopic anterior cruciate ligament (ACL) repair: A randomised study - Ritesh Roy; Gaurav Agarwal; Priyanka Ahuja; Ankita Mohta (Indian Journal of Anaesthesia)
Background and Aims: Anterior cruciate ligament (ACL) repair is a common sports-related surgery requiring early rehabilitation. Injection between the popliteal artery and the capsule of the knee (iPACK) provides analgesia to the posterior knee and, when combined with adductor canal block (ACB), can provide complete analgesia for knee surgery. A 4-in-1 block, a single injection, has been studied for analgesia in TKR but not ACL repair. This study was done with the objective of comparing the postoperative analgesia of iPACK + ACB versus 4-in-1 block in ACL repair. Methods: The study was conducted on 184 participants undergoing ACL repair in the age group of 18–70 years. Patients were randomly allocated to iPACK +ACB or 4-in-1 block. After the preoperative and intraoperative protocol, a guided nerve block was performed. The duration of motor blockade of spinal anaesthesia and pain scores were monitored using the visual analogue scale (VAS), and the time for first rescue analgesia was noted at 3, 6, 12, 24, and 36 hours. An independent sample t-test was used to find the association of all quantitative variables, and a Chi-square test was used to find the association of categorical variables with both groups of patients (P < 0.05). Results: VAS scores were statistically similar between the two groups at 3, 6, 12, and 24 hours but were significantly less at 36 hours in group B (P < 0.001). The time to perform the regional block was lower in group B, a single injection technique (P < 0.001). None of the patients showed muscle weakness in the postoperative period and could cooperate reasonably with physiotherapy. Conclusion: The 4-in-1 block provides non-inferior analgesia compared to the established iPACK plus ACB for arthroscopic ACL surgery.